2011
DOI: 10.1002/ctpp.201000002
|View full text |Cite
|
Sign up to set email alerts
|

Electric Charging in Dielectric Barrier Discharges with Asymmetric Gamma‐Coefficients

Abstract: A dielectric barrier discharge with different electrode surfaces is investigated and the dynamic evolution of surface charge on the dielectric surface is measured optically. It is found that the amount of surface charge after the positive and the negative half-cycle are not equal, i. e. a bias charge emerges. To understand this phenomenon, the transfered charge per half-cycle is estimated from the Paschen curve and the shape of the driving voltage waveform. It turns out that the charge bias is necessary to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…It must be noted that some electro-optic crystals have distinct differences from the classical dielectric barrier materials. The dielectric constant is considerable higher, the secondary electron emission coefficient is assumed to be smaller than for glass [98,236], and photo-induced transport of charges on the minutes-scale has been obtained for bismuth silicon oxide crystals [98,215,237].…”
Section: Methods and Techniquesmentioning
confidence: 99%
“…It must be noted that some electro-optic crystals have distinct differences from the classical dielectric barrier materials. The dielectric constant is considerable higher, the secondary electron emission coefficient is assumed to be smaller than for glass [98,236], and photo-induced transport of charges on the minutes-scale has been obtained for bismuth silicon oxide crystals [98,215,237].…”
Section: Methods and Techniquesmentioning
confidence: 99%
“…The discrepancy to the negative charge amount (−1.7 nC) was already pointed out in previous investigations [27,29]. Most likely, it indicates a bias caused by different secondary electron emission coefficients of the dielectrics used [42]. During the breakdown phase, the wide deposition of surface electrons on the anodic dielectric is revealed, unlike the centered accumulation of positive surface charges on the cathodic dielectric resulting in a ring of residual surface electrons.…”
Section: Surface Charge Dynamicsmentioning
confidence: 70%
“…This effect could be controlled by modulating the pulse parameters (to be explained in Figure ). Since, DBD plasma devices are commonly used in biomedical applications, the simulation with the low secondary electron emission coefficient γ=0.01 is also conducted for the pulsed microwave case. It is found that the pulsed microwave DBD plasma sustained by the same driving voltage (Von=150 V) produces as much energetic electrons as in the bare electrode case.…”
Section: Resultsmentioning
confidence: 99%